Why I Want to Join the Base: Examining Individual-level Motivational Factors in Recruiting Interviews - Wilson, Rebecca A. (Terrorism and political violence, 2025)
This article presents a targeted examination of the relationship between individual-level factors of potential recruits within vetting interviews of violent extremist group, The Base. Using first-hand accounts and examining the relationships among various motivational factors, we investigate the motivation to join. Results demonstrate the ways in which factors including grievance, integrative complexity, implicit motivation, and emotion jointly increase the likelihood of engagement. We further investigate how these factors relate need to belong, search for identity, and perceived injustice and inequality at the individual level. Our results support the contention that violent extremist ideologies are shaped and bolstered by a heightened level of binary thinking, stripped of complexity, and with an identifiable in-group/out-group dynamic in which grievance is salient. Of note, we find that sense of community and belonging are a substantially motivating factor for prospective members of The Base who seek to make sense of a complex world.